Cirurgia parendodôntica para remoção de lesão e material obturados extravasado: relato de caso - GOMES, Andreis Cristian (2021)
Parendodontic surgery is indicated in cases which the coronal approach was not favorable and the endodontic retreatment is not possible. In teeth with incomplete rhizogenesis the chance of endodontic treatment failure is high, due to the morphological characteristics of the tooth, and a surgical approach may be necessary for better prognosis. The objective of this case report is to present the parendodontic surgery as the ideal treatment, after a complete evaluation of the case and considering the limitations of the tooth with incomplete rhizogenesis, the presence of periapical lesion and excess of obturator material. In this manner, the success of the surgical approach can be concluded, in which was obtained the removal of the lesion and the extravasated obturator material, besides the adequate apical sealing of the tooth with open apex.